Biocatalytic Enantioselective Oxidation of Sec‐Allylic Alcohols with Flavin‐Dependent Oxidases. Issue 22 (10th October 2019) - Gandomkar, Somayyeh; Jost, Etta; Loidolt, Doris; Swoboda, Alexander; Pickl, Mathias; Elaily, Wael; Daniel, Bastian; Fraaije, Marco W.; Macheroux, Peter; Kroutil, Wolfgang
Abstract: The oxidation of allylic alcohols is challenging to perform in a chemo‐ as well as stereo‐selective fashion at the expense of molecular oxygen using conventional chemical protocols. Here, we report the identification of a library of flavin‐dependent oxidases including variants of the berberine bridge enzyme (BBE) analogue from Arabidopsis thaliana ( At BBE15) and the 5‐(hydroxymethyl)furfural oxidase (HMFO) and its variants (V465T, V465S, V465T/W466H and V367R/W466F) for the enantioselective oxidation of sec ‐allylic alcohols. While primary and benzylic alcohols as well as certain sugars are well known to be transformed by flavin‐dependent oxidases, sec ‐allylic alcohols have not been studied yet except in a single report. The model substrates investigated were oxidized enantioselectively in a kinetic resolution with an E‐value of up to >200. For instance HMFO V465S/T oxidized the ( S )‐enantiomer of ( E )‐oct‐3‐en‐2‐ol (1 a ) and ( E )‐4‐phenylbut‐3‐en‐2‐ol with E>200 giving the remaining ( R )‐alcohol with ee >99% at 50% conversion. The enantioselectivity could be decreased if required by medium engineering by the addition of cosolvents (e. g. dimethyl sulfoxide). Abstract :